SIMULATION Wi-Fi NETWORK WITH WIRELESS DISTRIBUTION SYSTEM (WDS) TOPOLOGY (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
At present, the need for internet access in public area using wireless connections is increasing drastically and this should be supported by good network infrastructure. Wireless network is one of the best alternative in building a practical internet network. WDS is a system to develop wireless internet network without having to use cable as its backbone for access point but instead utilize wireless path from its access point. The problems that often arise in the design of wireless LAN network is the poor signal received by the user due to the installation of an access point that is poor location-wise. This is because at some point it is very difficult to install Access point using cable because the distance is too far from the existing router. In this paper, we propose to use three scenario of WDS mode to compare its performance. We investigate three different topology policy models of the WDS Bridge point-to-point, WDS Bridge point to multipoint and WDS repeater. The use of these three topologies aims to reach locations that are not covered by wireless LAN network, in addition this method can save the use of network resources such as LAN cables. Based on the simulation results, it is found that the topology point to point gives better value but it generated higher delays. The delay generated on point to point is higher than other topologies. Meanwhile, the measurement results are not much different on topology point to multipoint with repeater topology. The point to multipoint topology is slightly better than the repeater of the three QoS parameters.